A spool of blue thread [large type] - Tyler, Anne (Random House Large Print, 2015)
"It was a beautiful, breezy, yellow-and-green afternoon." This is the way Abby Whitshank always begins the story of how she fell in love with Red that day in July 1959. The whole family--their two daughters and two sons, their grandchildren, even their faithful old dog--is on the porch, listening contentedly as Abby tells the tale they have heard so many times before. And yet this gathering is different too: Abby and Red are growing older, and decisions must be made about how best to look after them, and the fate of the house so lovingly built by Red's father. Brimming with the luminous insight, humor, and compassion that are Anne Tyler's hallmarks, this capacious novel takes us across three generations of the Whitshanks, their shared stories and long-held secrets, all the unguarded and richly lived moments that combine to define who and what they are as a family.